Forskolin rapidly enhances neuron‐like morphological change of directly induced‐neuronal cells from neurofibromatosis type 1 patients - Noriaki Sagata; Shin‐ichi Kano; Masahiro Ohgidani; Shogo Inamine; Yasunari Sakai; Hiroki Kato; Keiji Masuda; Takeshi Nakahara; Makiko Nakahara‐Kido; Shouichi Ohga; Masutaka Furue; Akira Sawa; et al. (Neuropsychopharmacology Reports, 2020)
Abstract Aim Neurofibromatosis type 1 (NF1) is a multifaceted disease, and frequently comorbid with neurodevelopmental disorders such as autism spectrum disorder (ASD) and learning disorder. Dysfunction of adenylyl cyclase (AC) is one of the candidate pathways in abnormal development of neuronal cells in the brain of NF1 patients, while its dynamic abnormalities have not been observed. Direct conversion technology can generate induced‐neuronal (iN) cells directly from human fibroblasts within 2 weeks. Just recently, we have revealed that forskolin, an AC activator, rescues the gene expression pattern of iN cells derived from NF1 patients (NF1‐iN cells). In this microreport, we show the dynamic effect of forskolin on NF1‐iN cells. Methods iN cells derived from healthy control (HC‐iN cells) and NF1‐iN cells were treated with forskolin (final concentration 10 μM), respectively. Morphological changes of iN cells were captured by inverted microscope with CCD camera every 2 minutes for 90 minutes. Results Prior to forskolin treatment, neuron‐like spherical‐form cells were observed in HC‐iN cells, but most NF1‐iN cells were not spherical‐form but flatform. Only 20 minutes after forskolin treatment, the morphology of the iN cells were dramatically changed from flatform to spherical form, especially in NF1‐iN cells. Conclusion The present pilot data indicate that forskolin or AC activators may have therapeutic effects on the growth of neuronal cells in NF1 patients. Further translational research should be conducted to validate our pilot findings for future drug development of ASD.